2013
DOI: 10.1109/led.2013.2272083
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characterization and Materials Stability Analysis of ${\rm La}_{2}{\rm O}_{3}/{\rm HfO}_{2}$ Composite Oxides on n-${\rm In}_{0.53}{\rm Ga}_{0.47}{\rm As}$ MOS Capacitors With Different Annealing Temperatures

Abstract: In this letter, a high-k composite oxide composed of La 2 O 3 and HfO 2 is investigated for n-In 0.53 Ga 0.47 As metal-oxide-semiconductor (MOS) capacitor application. The composite oxide was formed by depositing five layers of La 2 O 3 (0.8 nm)/HfO 2 (0.8 nm) on InGaAs with post deposition annealing at 500°C. The MOS capacitors fabricated show good inversion behavior, high capacitance, low leakage current, with excellent interface trap density (D it ) of 7.0 × 10 11 cm −2 eV −1 , small hysteresis of 200 mV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It is worth noting that the ϕB,n we obtained from the Schottky mechanism should be lower than the ideal barrier height by a value of △ϕB as shown in Figure 2. This gap can be explained by the Schottky barrier lowering effect [15,16]. It was found that Sample #1 presents a higher ϕB,n value than Sample #2, indicating that increasing the thickness of the Al2O3 film can suppress the accessibility of carriers to climb over the barrier to form a leakage current in the case of a fixed total thickness of laminated dielectric.…”
Section: Measurement and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the ϕB,n we obtained from the Schottky mechanism should be lower than the ideal barrier height by a value of △ϕB as shown in Figure 2. This gap can be explained by the Schottky barrier lowering effect [15,16]. It was found that Sample #1 presents a higher ϕB,n value than Sample #2, indicating that increasing the thickness of the Al2O3 film can suppress the accessibility of carriers to climb over the barrier to form a leakage current in the case of a fixed total thickness of laminated dielectric.…”
Section: Measurement and Discussionmentioning
confidence: 99%
“…In order to identify the impact of the thickness of the Al 2 O 3 inserting layer, we manufactured two kinds of samples with an oxide layer of HfO 2 (4 nm)/Al 2 O 3 (8 nm) laminated dielectrics (marked as Sample #1), and HfO 2 (8 nm)/Al 2 O 3 (4 nm) laminated dielectrics (marked as Sample #2), respectively. The detailed fabrication process is listed in Table 1 [16][17][18][19][20]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We controlled the ALD process circle to manufacture different dielectric thicknesses. A post-deposition annealing (PDA) process was applied to increase the quality of the oxide-semiconductor interface [14][15][16][17]. The process involved heating the film from ambient temperature to 380 • C in N 2 over 15 s, annealing for 60 s , and then cooling to ambient temperature over 300 s [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…HfO 2 has a high κ value of 25 and a high energy bandgap of 5.5 eV, and has been widely used as the gate oxide for III–V MOSFETs [2] in the past few years. Recent papers have reported an InGaAs device with excellent interface properties between high k oxides and the III–V semiconductor and demonstrated equivalent‐oxide‐thickness (EOT) scaling by using the new high k dielectric structure composed of La 2 O 3 and HfO 2 grown with the molecular beam deposition (MBD) technique [3]. In this Letter, a thermally stable multi‐layers La 2 O 3 /HfO 2 composite structure on InGaAs is reported with EOT scaling approaching 1 nm.…”
Section: Introductionmentioning
confidence: 99%